2006
DOI: 10.1002/hed.20436
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass S53P4 in frontal sinus obliteration: A long‐term clinical experience

Abstract: BAG appears to be a reliable frontal sinus obliteration material, providing favorable conditions for total bony sinus obliteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 37 publications
3
67
0
1
Order By: Relevance
“…Although bioactive glasses have been used for over 15 years with success in oral and maxillo-facial clinical applications (Froum et al, 1998;Peltola et al, 2006), limited benefits have been reported (Turunen et al, 2004;Wang et al, 2005). Recently, due to the growing evidence showing that strontium influences bone cells and bone metabolism in vitro and in vivo (Marie, 2006), melt-derived strontiumdoped bioactive glasses prepared from a base 45S5 bioglass have been developed and implanted in rat tibia bone marrow (Gorustovich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although bioactive glasses have been used for over 15 years with success in oral and maxillo-facial clinical applications (Froum et al, 1998;Peltola et al, 2006), limited benefits have been reported (Turunen et al, 2004;Wang et al, 2005). Recently, due to the growing evidence showing that strontium influences bone cells and bone metabolism in vitro and in vivo (Marie, 2006), melt-derived strontiumdoped bioactive glasses prepared from a base 45S5 bioglass have been developed and implanted in rat tibia bone marrow (Gorustovich et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive glasses are surface reactive biomaterials that, when in contact with physiological fluids, release soluble ionic products that have been suggested to stimulate in vitro osteogenesis (Xynos et al, 2000;Tsigkou et al, 2009). In addition, in vivo studies have demonstrated beneficial results from their use in various clinical situations (Froum et al, 1998;Anderegg et al, 1999;Froum et al, 2002;Peltola et al, 2006). After implantation, interaction with surrounding tissues results in a time-dependent alteration of the material's surface and the formation of a hydroxyl carbonate apatite layer that is very similar to the mineral phase of bone (Hench and Paschall, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…BAG S53P4 has been studied clinically in randomised prospective trials in bone tumour [27,28], trauma [29] and spine surgery [30,31]. Due to its antibacterial properties is has also been used in the treatment of severe chronic osteomyelitis, mastoiditis, spine infections and frontal sinus infections [21,[32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Gosain et al (6) presented a safety and efficacy report for bioactive glass for craniomaxillofacial reconstruction and supported the clinical applications of bioactive glasses in this area. Peltola et al (12) have a report on the use of bioactive glass particles to obliterate the frontal sinus in 30 patients over a 10-year period. Although there was some decrease in radiologic density of the obliteration material over time, they reported the material to be well tolerated with no loss of volume.…”
Section: Resultsmentioning
confidence: 99%